The Essence of Worldly Life in Q.S. Al-Ḥadīd (57): 20 (An Analysis Using Michael Riffaterre’s Heuristic and Hermeneutic Reading) - Ahmad Hizkil (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
This study aims to reveal the the essence of world life described in Q.S Al Hadid (57): 20 based on Michael RIffaterre's heuristic and hermeneutic reading. This research is included in the descriptive-qualitative research by making Q.S Al Hadid (57): 20 as the object of research as well as the source of the data. The theory used is Michael Riffaterre's semiotic theory which introduces heuristic and hermeneutic reading methods in interpreting a text. The data collection technique is a listening and note-taking technique. Meanwhile, the data analysis technique is descriptive-analytic. The results of this study indicate that the parable of the world mentioned in Q.S. Al Hadid (57): 20 is the essence of the real life of the world. That the life of this world is just a game and a negligent joke. The parables of the world are a form of displacing of meaning as in Riffaterre's theory. The regularity of the editors in every parable of the world is a picture of the phase of human life from childhood to adulthood and then death. This meaning is part of the form of creating meaning. The prioritization of